Eating disorders in Spanish acrobatic gymnasts based on sex and competitive level - Salas-Morillas, A.; Gutiérrez-Sánchez, Á.; Ariza-Vargas, L.; Vernetta-Santana, M. (Science of Gymnastics Journal, 2023)
The aim of this study was to assess the body composition and the risk of developing an eating disorder (ED) in two groups of Spanish elite acrobatic gymnasts. A cross-sectional descriptive study was conducted, where 130 acrobatic gymnasts aged 9 to 21 and registered with the Spanish federation voluntarily participated; 56 of them were competing at the international level and 74 at the national level. Height and weight measures were used to calculate body mass index (BMI) and skinfolds were measured to determine the percentage of body fat. The Eating Disorders Inventory (EDI-3-RF) was applied to assess the ED variables. The results revealed that the majority of gymnasts presented normal weight (BMI) and a low % body fat, and the international-level gymnasts showed lower values than national-level ones. 52.6% of the gymnasts in this study were at risk of developing an ED. As regards the scales, the scores related to drive for thinness were noteworthy, especially in women competing at the international level, who reported greater concern about weight and body image. The international-level gymnasts met most of the referring criteria; in particular, most senior gymnasts met criterion 3. There was an average percentage of gymnasts at risk of developing an ED. The risk factors were more noticeable among female international-level gymnasts, who presented greater drive for thinness and body dissatisfaction.